Developing talent in young people - Bloom, Benjamin S. (New York Ballantine Books, 1985)
The dramatic findings of a ground-breaking study of 120 immensely talented individuals reveal astonishing new information on developing talent in young people.
Includes bibliographies and index
Keywords: Achievement motivation in children